Association between the cumulative estimated glucose disposal rate and incident cardiovascular disease in individuals over the age of 50 years and without diabetes: data from two large cohorts in China and the United States - Jin Zhang; Ziyi Sun; Yufei Li; Yuhan Yang; Wenjie Liu; Mengwen Huang; Kuiwu Yao (Cardiovascular Diabetology)
Abstract Background The estimated glucose disposal rate (eGDR) has been linked to incident cardiovascular disease (CVD) in individuals without diabetes. However, few studies have accounted for long-term cumulative eGDR exposure. Objective The aim of this study was to explore whether long-term cumulative eGDR was independently associated with incident CVD in individuals over the age of 50 years and without diabetes. Methods This study used data from the China Health and Retirement Longitudinal Study (CHARLS) and Health and Retirement Study (HRS). The cumulative eGDR was calculated as the summation of the average eGDR for each pair of consecutive examinations multiplied by the time between these two consecutive visits, in years. The outcome was incident CVD. Cox proportional hazards regression models and restricted cubic spline (RCS) regression models were used to evaluate the association between cumulative eGDR and incident CVD. Results A total of 2430 participants from CHARLS and 2008 participants from HRS were included in the analysis. The median age of the participants in CHARLS at baseline was 59 years [IQR: 55–65 years], and 1205 (49.59%) were men. The median age of the participants in HRS at baseline was 64 years [IQR: 57–70 years], and 705 (35.11%) were men. The RCS regression model showed a negative and linear association between the cumulative eGDR and incidence of CVD (CHARLS: P < 0.001, P for nonlinearity = 0.248; HRS: P = 0.013, P for nonlinearity = 0.121). After multivariate adjustment, the higher levels of cumulative eGDR were independently associated with a lower risk of CVD (per SD, CHARLS: HR: 0.802, 95% CI: 0.716–0.898, HRS: HR: 0.791, 95% CI: 0.665–0.940, pooled analysis: HR: 0.799, 95% CI: 0.726–0.878). Conclusions A lower level of cumulative eGDR was associated with an increased risk of incident CVD in individuals over the age of 50 years and without diabetes. Continuous monitoring of cumulative eGDR exposure over time, based on consideration of traditional risk factors, may prove beneficial for the early identification and intervention of individuals at high risk of CVD. In regions with limited healthcare resources, among individuals with limited ability to access, process, and understand health information and services, cumulative eGDR may offer improved clinical applicability.